Spin squeezing em núcleos quadrupolares em ressonância magnética nuclear e Hamiltonianos de One-Axis Twisting com adição de termo do tipo interação dipolar - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
In this work, are analyzed the effects of the addition of a coupling term based on the dipole interaction between quadrupolar nuclei in NMR in the production of spin squeezing through One-Axis Twisting Hamiltonians. Several coupling regimes are addressed in the case of subsystems with angular momentum I = 7/2 and J = 3/2. It is verified through the dynamics addressed and by the minimum values of the spin squeezing parameter _S^2 as a function of the coupling intensity D that, despite significant changes in the dynamics, spin squeezed states are still encountered during the evolutions
Spin squeezing in quadrupolar nucleiin nuclear magnectic ressonance and one-Axis Twisting Hamiltonians with addition of a dipole-like interaction term
Keywords: Spin squeezing; Condensados de Bose-Einstein; Ressonância magnética nuclear; Hamiltonianos de OAT; Interação dipolar; Spin squeezing; Bose -Einstein condesates; Nuclear magnectic ressonance; OAT Hamiltonians; Dipolar inte; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA